Extreme thrombocytosis in systemic juvenile idiopathic arthritis. A case report - Alessandra Iacono; Monica Sprocati; Anna Lisa Giuliani; Francesco Di Virgilio; Caterina Borgna-Pignatti; Giuseppe Maggiore (BMC, 2019)
Abstract Background Systemic onset juvenile idiopathic arthritis (SoJIA) is a rare inflammatory disorder characterized by remitting fevers, evanescent rash, generalized lymphadenopathy, hepatomegaly/splenomegaly, and/or serositis. Case presentation Here we report the case of a 5 years-old girl with SoJIA complicated by severe thrombocytosis. Treatment with the Interleukin-1β (IL-1β) receptor antagonist Anakinra caused a fast reduction of blood platelets and of the associated systemic inflammatory response. Measurement of IL-1β, IL-6 and Tpo plasma levels at different time points confirmed the etiopathogenetic role of IL-1β in causing the thrombocytosis, while Tpo did not appear to be involved and this explains the excellent response to treatment with Anakinra. Conclusion The excellent response to treatment with the IL-1β receptor antagonist, suggests a key pathogenic role of IL-1β in thrombocytosis as well as in the associated systemic symptoms of inflammation.